Recovery of chlorophylls from spent biomass of Arthrospira platensis obtained after extraction of phycobiliproteins. (January 2019) - Tavanandi, Hrishikesh A.; Raghavarao, K.S.M.S.
Graphical abstract: Highlights: Spent biomass, left after C-PC & A-PC extraction, was used for chlorophyll recovery. Ethanol, a food grade solvent, was preferred achieving results at par with acetone. At standardized conditions, 82% of available chlorophyll could be extracted. Extraction time could be significantly reduced after standardization. Low-Humidity drying was employed as an alternative to freeze drying. Abstract: Extraction of chlorophylls has received scant attention or priority over phycobiliproteins from Arthrospira platensis . In fact extraction of chlorophylls from spent biomass (left after extraction of phycobiliproteins which goes as waste or underutilized) on drying, will improve the economics of the overall downstream processing. Ethanol (yield 5.75 mg/g, db), being a food grade solvent, was preferred over acetone and dimethyl sulfoxide in spite of their slightly better yields (5.85 mg/g, db). The best conditions were 100% concentration of ethanol, 1:8 S/L ratio, pH 6, 50 °C temperature and 1 h extraction time. An increase of 125% in yield besides reduction of 83.3% in extraction time (from 6 to 1 h) could be achieved at standardized conditions. Low-Humidity drying was observed to be a possible alternative to freeze drying for drying of spent biomass. Ultrasonication as pre-treatment and ethanol as solvent were found effective for extraction of chlorophylls from dry spent biomass.